2D‐Topology‐Seeded Graphitization for Highly Thermally Conductive Carbon Fibers. Issue 28 (3rd June 2022) - Ming, Xin; Wei, Anran; Liu, Yingjun; Peng, Li; Li, Peng; Wang, Jiaqing; Liu, Senping; Fang, Wenzhang; Wang, Ziqiu; Peng, Huanqin; Lin, Jiahao; Huang, Haoguang; et al.
Abstract: Highly thermally conductive carbon fibers (CFs) have become an important material to meet the increasing demand for efficient heat dissipation. To date, high thermal conductivity has been only achieved in specific pitch‐based CFs with high crystallinity. However, obtaining high graphitic crystallinity and high thermal conductivity beyond pitch‐CFs remains a grand challenge. Here, a 2D‐topology‐seeded graphitization method is presented to mediate the topological incompatibility in graphitization by seeding 2D graphene oxide (GO) sheets into the polyacrylonitrile (PAN) precursor. Strong mechanical strength and high thermal conductivity up to 850 W m − 1 K −1 are simultaneously realized, which are one order of magnitude higher in conductivity than commercial PAN‐based CFs. The self‐oxidation and seeded graphitization effect generate large crystallite size and high orientation to far exceed those of conventional CFs. Topologically seeded graphitization, verified in experiments and simulations, allows conversion of the non‐graphitizable into graphitizable materials by incorporating 2D seeds. This method extends the preparation of highly thermally conductive CFs, which has great potential for lightweight thermal‐management materials. Abstract : A 2D‐topology‐seeded graphitization strategy effectively generates a new species of highly thermally conductive carbon fibers. Strong mechanical strength and high thermal conductivity up to 850 W m − 1 K −1 are simultaneously realized, which are one order of magnitude more conductive than commercial PAN‐based carbon fibers. These fibers have great potential for lightweight thermal‐management materials, high‐power electronics, and energy storage.